2019
DOI: 10.1073/pnas.1811379116
|View full text |Cite
|
Sign up to set email alerts
|

Physical exertion exacerbates decline in the musculature of an animal model of Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a genetic disorder caused by loss of the protein dystrophin. In humans, DMD has early onset, causes developmental delays, muscle necrosis, loss of ambulation, and death. Current animal models have been challenged by their inability to model the early onset and severity of the disease. It remains unresolved whether increased sarcoplasmic calcium observed in dystrophic muscles follows or leads the mechanical insults caused by the muscle’s disrupted contractile machinery. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 56 publications
3
31
0
1
Order By: Relevance
“…Under standard assay conditions of 26 % w/w, we observed that animals burrow with a mean velocity of 1.14 mm/min and undulatory frequency of 0.07 Hz. In contrast, at 3 % w/v agar, animal velocity was found to be 2 mm/min [19] and at 9 % w/v agar the undulatory frequency was reported to be 0.2 Hz [16]. Additionally, 3D behavioral studies in 3 % w/v gelatin report a velocity of 5 mm/min [17].…”
Section: Pluronic As a Novel Medium For C Elegans Burrowingmentioning
confidence: 88%
See 4 more Smart Citations
“…Under standard assay conditions of 26 % w/w, we observed that animals burrow with a mean velocity of 1.14 mm/min and undulatory frequency of 0.07 Hz. In contrast, at 3 % w/v agar, animal velocity was found to be 2 mm/min [19] and at 9 % w/v agar the undulatory frequency was reported to be 0.2 Hz [16]. Additionally, 3D behavioral studies in 3 % w/v gelatin report a velocity of 5 mm/min [17].…”
Section: Pluronic As a Novel Medium For C Elegans Burrowingmentioning
confidence: 88%
“…In this section, we harness these capabilities to demonstrate that burrowing can be used in diverse applications. None of these demonstrative applications and the results thereof have been shown by prior burrowing studies [16][17][18][19][20]. Since our intent is to demonstrate the power of the assay platform we designed, we consider our results in each of these applications as laying foundation for future in-depth investigations.…”
Section: Pluronic-based Burrowing Assay Is Well Suited For Diversementioning
confidence: 99%
See 3 more Smart Citations